KORELASI KEPRIBADIAN GURU DAN AKHLAK SISWA DENGAN PRESTASI BELAJAR SISWA - Muhtadi; Joko Kristanto; Adibah (FAI- Undar, 2017)
This study aims to determine the correlation of teacher personality and student morals with student achievement in Islamic Junior High School Hidayatul Mubtadiin, Puri District, Mojokerto Regency.This research approach uses quantitative research. The research sample is the entire population of 42 respondents. The data collection instrument used a questionnaire/questionnaire.Based on the calculation of the data analysis above, it is obtained that the value of r Count = 0.031 with N = 100 and the level is obtained by the value of r in the table and compares the probability value of SPSS output with the probability value used by researchers (usually using 5% for social research). The value of rxy r table or SPSS output probability 0.05, then the item is valid. This means that the consequence is that the null hypothesis (Ho) which reads